(untitled) (CIPEEX, 2025)
Objective: The aim of this study was to compare agility in the 505 test before and after an eight-week intervention involving reduced games in futsal athletes without specific agility training. Materials and Methods: Thirty-one under-20 futsal athletes from IFPI Campus Teresina Central were evaluated, with a mean age of 16 ± 1.63 years, body mass of 58.70 ± 10.37 kg, and height of 1.72 ± 0.07 m, respectively. They underwent the 505 agility test before and after an 8-week intervention of reduced games. Results: The results showed that there was an improvement in time (seconds), as shown by the data, which consequently obtained improved results in the Pre [3.09 seconds (2.88–3.20)] and Post [2.94 seconds (2.87–3.10)] tests, demonstrating (Z = 2.460; p = 0.014), p>0.05. Conclusion: Eight weeks of reduced games improve agility performance in futsal athletes.